Violations of Expectations As Matter for the Believing Process - Angel, Hans-Ferdinand; Seitz, Rüdiger J. (Frontiers in Psychology, 2017)
For the purpose of this communication it is postulated that violation of expectation means a disturbing event or conflict interfering with a previously established mental state that affords a firm belief or confident feeling. According to this hypothesis a violation of an expectation contradicts predictions and intentions that have been attained on stored experiences, valuations, and actual mood. We will argue that the notion of belief as static or stable which is usually described by expressions such as “my belief” or “our general belief” has to be extended to accommodate the process of belief formation. The credition model emphasizes the procedural aspect of belief by which the “process of believing” becomes similar to other psychological processes. We will describe that the “violation of expectation” can be decoded from the credition perspective and has brain functional correlates.